EFEITOS DO EXERCÍCIO FÍSICO AQUÁTICO NOS FATORES DE RISCO NEUROPSICOLÓGICOS DE QUEDAS EM IDOSOS DA COMUNIDADE: ENSAIO CLÍNICO RANDOMIZADO - Dayane Melo Campos (2021)
Background: With physiological decline of aging, older people may have a higher rate and risk of falls. Consequences of falls include personal injuries and public costs with surgical interventions, medication and rehabilitation. Thus, the reduction of risk factors for falls is essential for older people’s health, and physical exercise is a therapeutic strategy. Among several resources, aquatic physical exercise can be used to reduce potentially modifiable risk factors for falls, such as cognitive decline, depressive and anxiety symptoms. There is a need for evidence to prove its effects. Objectives: To verify the effects of an aquatic physical exercise protocol on neuropsychological risk factors for falls in community-dwelling older people. Method: A randomized controlled, single-center, single-blind clinical trial was carried out with community-dwelling older people, aged over 65 years old and without cognitive impairment. Participants were randomly assigned to two groups (Aquatic Physical Exercise GEFA and Control GC). The GEFA performed the multicomponent exercise protocol and the CG received only monthly calls to monitor general health. The aquatic training had progressive intensity, according to the Modified Borg Effort Perception Scale (BORG-CR10), duration of 16 weeks, frequency of twice a week and one hour per session, on non-consecutive days. Participants were assessed at baseline and after 16 weeks of training. The assessment consisted of clinical and sociodemographic data, level of physical activity (modified Baecke Questionnaire for elderly), cognition measures (Addenbrooke's cognitive examination - revised version (ACE-R)), executive functions (Frontal Assessment Battery) and behavioral symptoms (Geriatric Depression Scale -short version and Cardioemotion Apparatus). For data analysis by intention to treat, a significance level of α = 0.05 was adopted and the SPSS software (20.0) was used. Results: The final sample consisted of 49 older people, 25 from the CG and 24 from the GEFA. Regarding neuropsychological factors of the total sample, there were no significant differences between groups in any variable. There were significant differences between moments, regardless of the group, in the total score of the ACE-R and memory domain. Both groups showed improvements in the total score, while the GEFA showed a better memory domain. When evaluating only participants who adhered at least 50% of the intervention, there was a significant improvement after 16 weeks in the total ACE-R score, especially in the GEFA. Conclusion: Aquatic physical exercise had positive effects on cognitive functions in community-dwelling older people, with potential to decrease risk of falls in this population